Effects of Dexamethasone on Contralateral Testicular Immune Response in Wistar Strain Rats with Unilateral Testicular Torsion - Kustono, Andri; Sudiana, I Ketut; Rizaldi, Fikri; Tarmono, Tarmono (Folia Medica Indonesiana, 2018)
The aim of this study was to prove the effects of dexamethasone on immune responses in rats with testicular torsion. This was an experimental study with post test only control group design. In this study, 27 rats were randomly divided into 3 groups. In normal or sham group (CN) orchidectomy was performed on the right testis on day 14. The positive control group (CP) had testicular torsion for 10 h, then manual detorsion was performed after 4 h, and on day 14 orchidectomy was performed on ipsilateral and contralateral testes. The treatment group (N) had testicular torsion for 10 h and received 10 mg/kgBW dexamethasone subcutaneously 30 minutes before manual detorsion 4 hours later, and on day 14 orchidectomy was performed to ipsilateral and contralateral testes. The spermatogonium count was calculated based on the average number of intratubular seminiferous tubule section observed in contralateral testicular incision with Haematoxiliyn Eosin (HE) staining. IgG count was calculated based on the average number of extratubular seminiferous tubules observed at 5 contralateral testicular incision with immunohistochemical staining (IHC). The number of spermatogonia was significantly different between CN and CP, CN and N, and CP and N (p<0.05). IgG production also showed significant differences between CN and CP, CN and N, as well as CP and N (p<0.05). In conclusion, administration of dexamethasone provides a protective effect on spermatogonium count and IgG production on a 10-hour testicular torsion.